Protocol to detect and quantify tumor hypoxia in mice using photoacoustic imaging - Tao Dai; Laurie J. Rich; Mukund Seshadri; Subhamoy Dasgupta (STAR Protocols, 2024)
Summary: Photoacoustic imaging (PAI) with co-registered ultrasound (US) is a hybrid non-invasive imaging modality that enables visualization and quantification of tumor hypoxia in live animals. Here, using a breast tumor xenograft model as an example, we present a stepwise protocol describing animal preparation, positioning, instrument setup, and US-PAI image acquisition procedures. This protocol also guides through detailed data analysis, explains functional readouts obtained from PAI, and discusses the potential application of the technology to study the hypoxic tumor microenvironment.For complete details on the use and execution of this protocol, please refer to Dai et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.